PERBANDINGAN KINERJA PADA BANGUNAN DENGAN SISTEM DINDING GESER DAN VISCOUS DAMPER - Erwin Rommel; Alfin Bena Tedha; Aulia Indira Kumalasari (LPPM Universitas Negeri Jakarta, 2025)
This study was conducted to evaluate the stability and performance of a building using a shear wall system with a building that applies FVD as a seismic damper system. The stability parameters analyzed include displacement, drift ratio, and storey drift. Meanwhile, the structural performance is analyzed based on the number of phases, hysteresis energy generated, and structural performance level. Numerical modeling of the building structure was conducted, and then earthquake loading simulations were carried out using ChiChi, Kobe, and Yushu earthquakes that had been scaled according to the dynamic response analysis procedure. The results show that the use of FVD as an energy dissipation system has significant potential in improving the performance and stability of structures. The performance of this system is shown to match, and in some aspects even compete, the effectiveness of shear walls in reducing the seismic response of building structures. Therefore, FVDs can be considered an efficient alternative in earthquake-resistant building design, especially in structures that require higher flexibility without sacrificing energy dissipation capacity.